2009
DOI: 10.1007/s11746-009-1431-2
|View full text |Cite
|
Sign up to set email alerts
|

Wild Brazilian Mustard (Brassica juncea L.) Seed Oil Methyl Esters as Biodiesel Fuel

Abstract: Wild mustard (Brassica juncea L.) oil is evaluated as a feedstock for biodiesel production. Biodiesel was obtained in 94 wt.% yield by a standard transesterification procedure with methanol and sodium methoxide catalyst. Wild mustard oil had a high content of erucic (13(Z)-docosenoic; 45.7 wt.%) acid, with linoleic (9(Z), 12(Z)-octadecadienoic; 14.2 wt.%) and linolenic (9(Z), 12(Z),15(Z)-octadecatrienoic; 13.0 wt.%) acids comprising most of the remaining fatty acid profile. The cetane number, kinematic viscosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(47 citation statements)
references
References 26 publications
4
40
1
Order By: Relevance
“…Winter canola can be grown successfully for biodiesel production 4,5 . The biodiesel advantages include its low sulphur content, no net CO 2 emission compared to convenAbstract: There is increased interest in winter canola as an oilseeds crop for production of oil or biodiesel in the southeastern United States, but research has been limited.…”
Section: Introductionmentioning
confidence: 99%
“…Winter canola can be grown successfully for biodiesel production 4,5 . The biodiesel advantages include its low sulphur content, no net CO 2 emission compared to convenAbstract: There is increased interest in winter canola as an oilseeds crop for production of oil or biodiesel in the southeastern United States, but research has been limited.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the morphological characters it had been identified as S. arvensis hatched from eggs exposed to volatiles from soil amended with different doses the leaf meal (a) and whole seed meal (b) of the wild mustard (Lorenzi 2000), but the chromosome count revealed that it maybe B. juncea (Jham et al 2009). The presence of high amounts of sinigrin compared to gluconapin and gluconasturtiin, also suggests that this weed plant maybe related to B. juncea, which is known to have sinirgin as the major GLN, although its concentration differs considerably among the cultivars and genotypes (Kirkegaard et al 1996;Mayton et al 1996;Lazzeri et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It has no commercial value although its seeds contain about 35% oil. In studies aimed at finding its utility, its seed oil was characterized and found to be a good biodiesel, suggesting that it can be cultivated as biodiesel crop (Jham et al 2009). It belongs to Brassicaceae family, and based on morphological characteristics this weed mustard had been considered as Sinapis arvensis L. (Lorenzi 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The economic value of the plant is mainly due to its widespread uses to produce fixed oils from its seeds, which still remains to be the main source of edible vegetable oils in many countries and cultural groups. Mustard seeds and oil are now also being explored for producing bio-fuels and diverse other commercial purposes (Jham et al, 2009). …”
Section: Fixed Oilsmentioning
confidence: 99%